Evolution of CaCu3Ti4O12 varistor properties during heat treatment in vacuum - Marques, V. P. B.; Ries, A.; Simoes, A. Z.; Ramirez, M. A.; Varela, José Arana [UNESP]; Longo, Elson [UNESP] (Elsevier B.V., 2007)
Calcium copper titanate (CaCu3Ti4O12) ceramic varistors were prepared by solid-state method. The samples were several times heat treated in vacuum and the evolution of electrical characteristics were monitored by current density versus electric field measurements and impedance spectroscopy. Repeated heat treatments in vacuum (900 degrees C for 1 h, 0.01 Torr) lead to a desorption of oxygen adsorbed at the grain boundaries and consequently to a degradation of the varistor properties. During further successive heat treatments some oxygen from the grain interior moves to the grain boundary thereby partially restoring the varistor properties. (c) 2006 Elsevier Ltd and Techna Group S.r.l. All rights reserved.
Keywords: varistors; calcium copper titanate